STRATEGI PENGUSAHA KAYU DOLOG DI DALAM MENYIKAPI PENJUALAN KAYU ILLEGAL LOGING, STUDI KOMPARASI PENGUSAHA KAYU DOLOG KABUPATEN JEPARA - Gun Sudiryanto (Jurnal DISPROTEK, 2016)
The issue of illegal logging affects the financial loss for an enterpreneur of wood in Jepara in which the issue frequently becomes a game object for unresponsible people. It gives a burden for enterpreus themselves wherein dolog woods become difficult in a good quality and price. The purpose of this study are 1) to establish standard sales price of dolog woods among wood enterpreneurs, 2) to restore the society??s faith toward the practice of buying and selling of dolog woods among wood enterpreneurs in Jepara. The study was conducted in the district of Jepara. The object of research was wood enterpreneursin Jepara. This study used qualitative research (field research) including direct observation and interviews with dolog wood enterpreneurs. The research intruments are: 1) The policy of the organization, 2) government regulations, 3) The price competition, 4) market conditions. The technique of daya analysis used comparative study supported by SWOT analysis. The results of the research are: 1) the price standardization of dolog wood, 2) an improvement of the quality of dolog woods, 3) the increse of eficiency and effectivity in every activities of dolog woods trade. Meanwhile, the recommendation and suggestion from the writer are 1) The development of facilities and infrastructure toward consumer as well as the service in one place, 2) the need to increase wood enterpreneurs profesionalism in conducting their business, thus, there is no dependency only because of one segment of market. Keywords: strategy, enterpreneurs, dolog, illegal, logging. Isu illegal logging mengakibatkan kerugian bagi pengusaha kayu Jepara, dimana isu tersebut seringkali menjadi obyek permainan bagi oknum-oknum yang tidak bertanggung jawab. Hal ini memberikan beban tersendiri bagi pengusaha, dimana kayu dolog makin sulit untuk diperoleh dengan kualitas dan harga yang sesuai. Tujuan penelitian 1) Terbentuknya standar harga penjualan kayu dolog dalam lingkungan pengusaha kayu Jepara, 2) Mengembalikan tingkat kepercayaan masyarakat terhadap praktek jual beli kayu dolog di lingkungan pengusaha kayu Jepara. Penelitian dilakukan di Kabupaten Jepara, obyek penelitian pengusaha kayu dolog di Kabupaten Jepara. Penelitian ini adalah kualitatif di lapangan (field research) berupa observasi langsung dan wawancara dengan pengusaha kayu dolog. Instrumen penelitian: 1) Kebijaksanaan organisasi, 2) Peraturan Pemerintah, 3) Persaingan harga, 4) Kondisi pasar. Teknik analisis data menggunakan studi komparasi yang didukung dengan analisis SWOT. Hasil penelitian adalah: 1) Standarisasi harga kayu dolog, 2) Meningkatkan kualitas kayu dolog, 3) Peningkatan efisiensi dan efektifitas dalam setiap kegiatan perdagangan kayu dolog. Sedangkan rekomendasi serta saran dari penulis adalah 1) Peningkatan sarana dan prasarana pelayanan terhadap konsumen, dengan penyediaan pelayanan dalam satu tempat, 2) Perlunya meningkatkan profesionalisme pengusaha kayu dolog di dalam menjalankan usahanya, sehingga tidak akan terjadi ketergantungan hanya ada pada satu segmen pasar saja. Kata kunci: strategi, pengusaha, dolog, illegal, logging